Optimizing Service Quality and Promotional Strategies to Increase Sales Visibility at Suzuki Laksda Sumber Baru Mobil Yogyakarta - Rachmawati, Putri Agustina; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this community service is to increase product sales at Suzuki Laksda Sumber Baru Mobil Yogyakarta through optimizing service quality and effective promotional strategies. The method used in this community service activity is through a systematic approach to the work program that is carried out in a planned and effective manner. Through several stages from survey and preparation, planning, work program implementation, and program evaluation. The result of this community service activity is to increase the knowledge and skills of Suzuki Laksda Sumber Baru Mobil Yogyakarta in optimizing the quality of its services to consumers and more creative promotional strategies in order to support marketing activities, so as to increase its competitiveness in the automotive field.